Formulation and evaluation of factorial design based sulfasalazine-loaded ethosomal gel for rheumatoid arthritis - Sanjaikumar D; Anasuya Patil; Hemanth G (Creative Pharma Assent, 2026)
Background: Oral administration of sulfasalazine for rheumatoid arthritis is associated with limitations that reduce therapeutic effectiveness. Transdermal delivery using ethosomal vesicles offers a promising strategy to enhance skin penetration and provide localized therapeutic effects. Methodology: Sulfasalazine-loaded ethosomes were formulated using the cold method and optimized using a 3² full factorial design across nine experimental trials. The formulations were characterized for vesicle size, polydispersity index (PDI), zeta potential, entrapment efficiency, and morphology using atomic force microscopy (AFM). The optimized ethosomal formulation was incorporated into a 1% Carbopol 934 gel to prepare the ethosomal gel (EGL). Ex vivo permeation studies were performed using rat skin to compare EGL with a conventional gel (CGL), and flux and permeability coefficients were calculated. Anti-inflammatory activity was assessed in Sprague–Dawley rats. Results and Discussion: Particle sizes ranged from 98.3 ± 2.37 nm to 187.7 ± 3.12 nm, with a negative zeta potential ranging between –24.2 ± 2.56 mV and –32.6 ± 1.35 mV. The entrapment efficiency ranged from 85.33 ± 3.84% to 94.62 ± 1.34%. Vesicles displayed smooth and spherical surfaces. In vitro drug release studies of the ethosomal gel formulations lasted 12 hours, revealing controlled release of sulfasalazine and enhanced ex vivo permeation in the optimized formulation. In vivo studies showed that EGL produced a greater reduction in inflammation compared to CGL. Conclusion: The developed ethosomal gel demonstrated enhanced skin permeation and anti-inflammatory efficacy, making it a promising transdermal delivery system for sulfasalazine in the management of rheumatoid arthritis.